The therapeutic potential of sphingolipids for cardiovascular diseases - Ya'ar Bar, Sapir; Pintel, Noam; Abd Alghne, Hesen; Khattib, Hamdan; Avni, Dorit (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases (CVDs) are the leading cause of morbidity and mortality worldwide and Inflammation plays a critical role in the development of CVD. Despite considerable progress in understanding the underlying mechanisms and various treatment options available, significant gaps in therapy necessitate the identification of novel therapeutic targets.Sphingolipids are a family of lipids that have gained attention in recent years as important players in CVDs and the inflammatory processes that underlie their development. As preclinical studies have shown that targeting sphingolipids can modulate inflammation and ameliorate CVDs, targeting sphingolipids has emerged as a promising therapeutic strategy. This review discusses the current understanding of sphingolipids' involvement in inflammation and cardiovascular diseases, the existing therapeutic approaches and gaps in therapy, and explores the potential of sphingolipids-based drugs as a future avenue for CVD treatment.